Robotics in MRI-Guided Interventions. Issue 1 (February 2018) - Hata, Nobuhiko; Moreira, Pedro; Fischer, Gregory
Abstract : Abstract: Robots have been found to be a useful tool in magnetic resonance imaging (MRI)-guided intervention. The utility of robots in MRI-guided therapy ranges from aid for precision targeting to high-dexterity surgical tools to improve or even enable new MRI-guided therapy options. The objective of this article is to review the technical aspects of robotics in MRI-guided interventions, highlight the role of MRI robots in prostate interventions, and finally discuss the future contribution of emerging robotics technology useful in MRI-guided intervention.